A voltage-gated potassium channel in human T lymphocytes. - Cahalan, M D (1985)
Human peripheral T lymphocytes were studied at 20-24 degrees C using the gigaohm seal recording technique in whole-cell or outside-out patch conformations. The predominant ion channel present under the conditions employed was a voltage-gated K+ channel closely resembling delayed rectifier K+ channels of nerve and muscle. The maximum K+ conductance in ninety T lymphocytes ranged from 0.7 to 8.9 nS, with a mean of 4.2 nS. The estimated number of K+ channels per cell is 400, corresponding to a density of about three channels/micron2 apparent membrane area. The activation of K+ currents could be fitted by Hodgkin-Huxley type n4 kinetics. The K+ conductance in Ringer solution was half-maximal at -40 mV. The time constant of K+ current inactivation was practically independent of voltage except near the threshold for activating the K+ conductance. Recovery from inactivation was slow and followed complex kinetics. Steady-state inactivation was half-maximal at -70 mV, and was complete at positive potentials. Permeability ratios, relative to K+, determined from reversal potential measurements were: K+(1.0) greater than Rb+(0.77) greater than NH4+(0.10) greater than Cs+ (0.02) greater than Na+(less than 0.01). Currents through K+ channels display deviations from the independence principle. The limiting outward current increases when external K+ is increased, and Rb+ carries less inward current than expected from its relative permeability. Tail current kinetics were slowed about 2-fold by raising the external K+ concentration from 4.5 to 160 mM, and were 5 times slower in Rb+ Ringer solution than in K+ Ringer solution. Single K+ channel currents had two amplitudes corresponding to about 9 and 16 pS in Ringer solution. Replacing Ringer solution with isotonic K+ Ringer solution increased the unitary conductance and resulted in inward rectification of the unitary current-voltage relation. Comparable effects of external K+ were seen in the whole-cell conductance and instantaneous current-voltage relation. Several changes in the K+ conductance occurred during the first few minutes after achievement of the whole-cell conformation. Most are explainable by dissipation of a 10-20 mV junction potential between pipette solution and the cytoplasm, and by the use of a holding potential more negative than the resting potential. However, inactivation of K+ currents became faster and more complete, changes not accounted for by these mechanisms. K+ efflux through open K+ channels in intact lymphocytes, calculated from measured properties of K+ channels, can account for efflux values reported in resting lymphocytes, and for the increase in K+ efflux upon mitogenic stimulation.(ABSTRACT TRUNCATED AT 400 WORDS)